Thrombin generation in severe haemophilia A and B: the endogenous thrombin potential in platelet-rich plasma - Siegemund, Thomas; Petros, Sirak; Siegemund, Annelie; Scholz, Ute; Engelmann, Lothar (Thrombosis and Haemostasis, 2003)
Thrombin generation was investigated in platelet-rich plasma (PRP) from 11 healthy controls, 17 patients with severe haemophilia A and 7 patients with severe haemophilia B. Mean endogenous thrombin potential (ETP) in arbitrary fluorescence units (FU) was 226.9 ± 44.6, 186.4 ± 22.5, 154.2 ± 41.3 in controls, haemophilia A and B, respectively, all at a platelet count of 200 × 109/l (p = 0.004 for controls vs.haemophilia A, p = 0.003 for controls vs. haemophilia B, no significant difference between haemophilia A and B). The contribution of FVIII to thrombin generation in haemophilia A was 1.31 ± 0.16 FU/% of FVIII:C activity , while for FIX in haemophilia B this was 0.80 ± 0.21 FU/% of FIX activity. There was an almost linear relationship between increasing platelet count and thrombin generation up to a mean platelet count of 100 × 109/l. Further increase in platelet count has only a marginal influence on thrombin generation. Platelets increase ETP in haemophilia A by 0.184 ± 0.022 FU/109platelets/l and in haemophilia B by 0.319 ± 0.085 FU/109platelets/l, and this was significantly different between the two groups (p = 0.0002). This influence of platelets diminishes with increasing concentration of either FVIII or FIX. In conclusion, there is a difference in thrombin generation between haemophilia A and B, and this may be attributed to the role of platelets in the assembly of the tenase complex on their surface.
Keywords: Thrombin generation; haemophilia; factor VIII; factor IX; platelets